2017
DOI: 10.1111/spol.12307
|View full text |Cite
|
Sign up to set email alerts
|

Geographies of Local Government Stress after the Great Recession

Abstract: Local governments in the USA are facing increased levels of fiscal stress after the Great Recession. We conducted a national survey in 2012 to assess differences in sources of stress and service delivery responses (privatization, inter-municipal co-operation, and public delivery) across places. Our discriminant analysis on 1,889 US cities and counties contributes to the literature on state rescaling. We differentiate three types of stress: fiscal, housing market decline and demographic. Fiscal stress and demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 60 publications
0
60
0
Order By: Relevance
“…They also find that overall, cross‐state inequality is consistent over time, but that the changes associated with the Personal Responsibility and Work Opportunities Reconciliation Act of 1996 yielded greater cross‐state inequality in related programming. Kim and Warner () have identified similar results of state decentralization to the local level. They examine the response of cities and counties to fiscal stress introduced by the Great Recession and find evidence that devolution of responsibility, reductions of state assistance, and constraints on local revenue‐raising authority have resulted in spatial inequalities in service provision.…”
Section: What Factors Influence Redistributive Social Policy Decisions?mentioning
confidence: 68%
“…They also find that overall, cross‐state inequality is consistent over time, but that the changes associated with the Personal Responsibility and Work Opportunities Reconciliation Act of 1996 yielded greater cross‐state inequality in related programming. Kim and Warner () have identified similar results of state decentralization to the local level. They examine the response of cities and counties to fiscal stress introduced by the Great Recession and find evidence that devolution of responsibility, reductions of state assistance, and constraints on local revenue‐raising authority have resulted in spatial inequalities in service provision.…”
Section: What Factors Influence Redistributive Social Policy Decisions?mentioning
confidence: 68%
“…Alberta) showed less privatization. The South and West also have larger municipalities (in population) and more poverty (Kim and Warner ), and prior research has found that privatization is lower in such higher cost markets (Hefetz et al ).…”
Section: Results: Local Government Service Provision and Deliverymentioning
confidence: 99%
“…Fiscal stress has led to the search for alternative revenue sources. Developer impact fees, user fees, sales taxes, hotel taxes, and tax increment financing have become popular, especially in fast‐growing markets (Weber ; Kim and Warner ). Some scholars see the use of these financial tools as acquiescence to a neoliberal ethos that shifts fiscal burdens to the household (Peck , ).…”
Section: Public Services After the Great Recessionmentioning
confidence: 99%
“…In many US states there were substantial cuts in services, wages, benefits and employment at local level (Wolff & Fraad-Wolff, 2011), all of which have had negative effects on local economies (Glasmeier & Lee-Chuvala, 2011). Now there is a call for more redistributive state policies given that decentralisation of services provision by US local authorities has exacerbated spatial inequalities -in particular, rural disadvantage has deepened (Kim & Warner, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%